Analisa Strategi Lingkungan Eksternal yang Dilakukan PT Telekomunikasi Indonesia, Tbk. - Adi Neka Fatyandri; Jollin, Jollin; Nurul Jofia; Silvia Salim; Winda Fionita Sitorus; Yessa Natasha (STEKOM PRESS, 2023)
In facing business competition, PT Telkom implements a strategy to be able to compete in the international market so that the company's capabilities and advantages competitive companies in the face of increasing competition in the international market effective. This study aims to determine the marketing strategy, the five forces analysis, industrial environment and SWOT analysis at PT Telkom. Besides that, identify the factors that become strengths and weaknesses as well opportunities and threats for this company. The analysis used in the research. This is a qualitative and descriptive descriptive analysis. By doing This external environmental analysis can evaluate PT Telkom's competitive strategy in achieving sustainable growth. By utilizing the porter five forces It is hoped that PT Telkom will be able to recognize its competitive position and improve competitive advantage to win the market. Keywords: Analysis, external, factors, PT Telkom.